PENGARUH KURIKULUM MERDEKA TERHADAP PENCAPAIAN SDGS MELALUI PENGEMBANGAN KARAKTER SISWA : STUDI LITERATUR - Annisa Nathania Putri Dewi; Deswita Sudaryanti; Ichsan Fauzi Rachman (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2025)
Quality education is a primary development goal that continues to be pursued by the government, private sector, educational institutions, and the general public. This study aims to provide a strategic overview of efforts to improve the quality of education in Indonesia, particularly in relation to the achievement of the Sustainable Development Goals (SDGs). The method used is a qualitative approach through literature review from various relevant journals and scientific articles. The findings indicate that the low quality of education in Indonesia is caused by both structural and cultural factors, as well as the unequal access to quality education. Therefore, professional development for educators and the implementation of effective pedagogical approaches are essential. Additionally, the integration of STEM-based electronic modules in science learning has proven effective in enhancing students’ critical thinking skills and strengthening the profile of Pancasila Students. Through synergy between SDG strategies, teacher capacity development, and innovative learning approaches education in Indonesia is expected to grow in a more equitable and high-quality manner.